Toward a Politics of "Raw Dicks": Authenticity, the Alt-Self, and New Understandings of the Phallus. (1st March 2022) - Ashford, Chris; Longstaff, Gareth
Abstract: Law arguably shapes contemporary culture and phallic politics. In England and Wales, like much of the Global North, the second half of the twentieth century and early twenty-first century saw a general shift from a criminal legal framework that understood sexuality as sexual acts to a civil law framework that seeks to privilege institutions - notably marriage - and lifestyle as signifiers of sexuality. This article contributes to legal and cultural understandings of the phallus, specifically the "raw dick, " as key to understanding the self-representational spaces of "authentic" and "alt" selves on social media. It situates the "raw dick" as the locus of this cultural, legal, and social exchange in which the legal outlaw of male phallic desire has been incorporated into queer citizenship. We argue that the aesthetics of the alt-self provides us with new and important ways to understand the phallus and its relationship to sex and sexuality.